Variations in Anatomical Position of Vermiform Appendix in Pakistani Population - Hina Jabeen, Romaiza, Maria Malik, Muhammad Kamran, Hira Ahmed, Shazia Fahim (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To study diversity in position and length of vermiform appendix in human body to manage the patients properly presenting with acute appendicitis. Methods: This is a cross sectional study conducted on 240 bodies. Study was conducted in anatomy department of Dow University of health sciences. Study was completed in one year duration from January 2021 to December 2021. Site and length of vermiform appendix was observed in dead bodies undergoing autopsy. Sample size was calculated using WHO sample size calculator. Consecutive sampling technique was used for sample selection. Data was analyzed using SPSS software (version-20) and chi-square test was applied on the collected data. Result: Total 240 bodies were studied for the anatomical position of appendix, including 156(65%) males and 84(35%) females. Mean age was 34.6 ± 5.2 years with the range of ages as 8-65 years. Mean length of the appendix was 92.6 ± 2.5 mm in men and 85.3 ± 4.7 mm in women. Pelvic position was the most common position of appendix found in 122(50.8%) bodies. Conclusion: High incidence of anterior position of appendix in Pakistani population describe that diagnosis of acute appendicitis can be made sooner and easier in our population with less complications like missed diagnosis, gangrene and perforation as compared to other populations.